Disease burden and attributable risk factors of major depressive disorder in China, Japan, and South Korea from 1990 to 2021 and its prediction to 2035 - Yifan Wang; Jingwen Zhu; Jihong Zhou (Frontiers in Public Health)
ObjectiveTo analyze the disease burden of major depressive disorder (MDD) and risk factors associated with MDD in China, Japan, and South Korea(CJK) from 1990 to 2021, to explore the effects of age, period, and cohort on the disease burden of MDD, and to predict the burden of MDD in CJK from 2021 to 2035.MethodsThe Global Burden of Disease 2021 (GBD) database was searched to collect the incidence, prevalence, disability-adjusted life years (DALYs), and risk factors of MDD in CJK. The respondents were selected from the Global, China, Japan, and South Korea. The respondents’ disease was major depressive disorder. The respondents’ gender was male, female, and both. The time was selected from 1990 to 2021. The age was selected from the whole age group (less than 5 years old to over 95 years old). Trends in MDD burden from 1990 to 2021 were analyzed using Joinpoint 4.9.1.0. Age-period-cohort (APC) analyses were performed using the APC Web Tool. Bayesian age-period-cohort analyses (BAPC) were performed using R4.4.1.ResultsJapan had the highest burden of MDD, followed by South Korea, and China had the lowest burden of MDD; The average annual percentage change (AAPC) of MDD burden indicators in China was less than 0, while in Japan and South Korea it was greater than 0. In 2021, middle-aged people aged 55–59 years had the highest burden of MDD in China, while in Japan and South Korea, young people aged 20–29 years had the highest burden of MDD, and the burden of MDD was higher among females than males in CJK from 1990 to 2021; APC analyses showed that the net drifts, local drifts, and RR values of the MDD burden indicators in CJK in terms of age, period, and cohort effects were closely related to the economic forms and aging populations; MDD had 3 levels and 5 risk factors; The burden of MDD in China would be in a decreasing trend between 2021 and 2035, and the burden of MDD in Japan and South Korea would be in a decreasing trend between 2021 and 2022, and an increasing trend between 2022 and 2035.ConclusionThere are both commonalities and differences in the burden of MDD in CJK, while the current burden of MDD in CJK is lower than the global average. Compared with Japan and South Korea China has a lower burden of MDD, but all three countries still face enormous challenges in the prevention and control of MDD.